Genetic population study of Y-chromosome markers in Benin and Ivory Coast ethnic groups. (November 2015) - Fortes-Lima, Cesar; Brucato, Nicolas; Croze, Myriam; Bellis, Gil; Schiavinato, Stephanie; Massougbodji, Achille; Migot-Nabias, Florence; Dugoujon, Jean-Michel
Highlights: 286 West Africans from five ethnic groups were typed for 17 Y-STRs and 96 Y-SNPs. Statistical analyses show close genetic distances between groups from Ivory Coast and Benin. Significant genetic differentiation was observed between Yoruba groups from Benin and Nigeria. Abstract: Ninety-six single nucleotide polymorphisms (SNPs) and seventeen short tandem repeat (STRs) were investigated on the Y-chromosome of 288 unrelated healthy individuals from populations in Benin (Bariba, Yoruba, and Fon) and the Ivory Coast (Ahizi and Yacouba). We performed a multidimensional scaling analysis based on F ST and R ST genetic distances using a large extensive database of sub-Saharan African populations. There is more genetic homogeneity in Ivory Coast populations compared with populations from Benin. Notably, the Beninese Yoruba are significantly differentiated from neighbouring groups, but also from the Yoruba from Nigeria ( F ST > 0.05; P < 0.01). The Y-chromosome dataset presented here provides new valuable data to understand the complex genetic diversity and human male demographic events in West Africa.